My Math Forum Simplification Normal Form - predicate logic

 Applied Math Applied Math Forum

 October 11th, 2014, 01:16 AM #1 Newbie   Joined: Oct 2014 From: Mauritius Posts: 1 Thanks: 0 Simplification Normal Form - predicate logic Hi! Can you please help me solve this question? (p → (q Λ r V s)) → ((p → q) V (r V s)) Convert into Disjunctive Normal Form(DNF) and Conjunctive Normal Form(CNF). Thank you in advance..
 October 11th, 2014, 06:17 AM #2 Senior Member   Joined: Dec 2013 From: Russia Posts: 327 Thanks: 108 Have you seen any examples of similar problems? What have you tried? Is q Λ r V s parsed as (q Λ r) V s or as q Λ (r V s)? Are you allowed to use truth tables? Then construct a truth table and select rows where the value of the formula is 1. For example, suppose this happens when p = T, q = F, r = T and s = F. To such row corresponds the disjunct $p\land \neg q\land r\land\neg s$. Collect all such disjuncts into a disjunction. That would be the DNF.

 Tags form, logic, normal, predicate, simplification

,
,

what is conjuctive normal form in predicate logic

Click on a term to search for related topics.
 Thread Tools Display Modes Linear Mode

 Similar Threads Thread Thread Starter Forum Replies Last Post skaur Applied Math 1 January 6th, 2014 05:51 PM mohitpd Applied Math 0 October 26th, 2013 07:45 PM pavankumar.thati Applied Math 0 April 16th, 2013 09:26 AM pinkcheese Applied Math 0 November 22nd, 2010 08:40 PM Zhai Applied Math 7 February 22nd, 2010 06:32 PM

 Contact - Home - Forums - Cryptocurrency Forum - Top